Árangur lungnabrottnámsaðgerða við lungnakrabbameini á Íslandi - Húnbogi Þorsteinsson; Steinn Jónsson; Hörður Alfreðsson; Helgi J. Ísaksson; Tómas Guðbjartsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) OBJECTIVE: Study the indications, complications and surgical outcome of pneumonectomy for non small cell lung cancer (NSCLC) in Iceland MATERIAL AND METHODS: A retrospective study of all pneumonectomies performed for NSCLC in Iceland from 1988 to 2007. Information was obtained from medical records and data on operative indications, postoperative TNM stage, complications, survival and survival predictors was analysed. RESULTS: 77 patients (64% males) with mean age of 62.3 yrs. were operated on, 44% on the right side. Mediastinoscopy was performed in 31% of cases. Most patients were stage I or II (58%), but 17 and 21% were stage III A and IIIB, respectively. Mean operation time was 161 min., bleeding 1.1 L and hospital stay 11 days. Atrial fibrillation (21%), pneumonia (6.5%), empyema (5.5%) and respiratory failure (5%) were the most common complications. Three (3.9%) patients died within 30 days from surgery. Five year survival was 20.7%. Age, history of COPD, adenocarcinoma histology and advanced TNM stage were independent predictors of poor survival. CONCLUSIONS: Pneumonectomies for NSCLC in Iceland have a low rate of complications and operative mortality. However, long term survival is lower than expected, and many patients (27%) were in advanced stages. This is most likely due to inadequate preoperative staging. TILGANGUR: Kanna árangur og ábendingar lungnabrottnámsaðgerða (pneumonectomy) við lungnakrabbameini á Íslandi. EFNIVIÐUR OG AÐFERÐIR: Afturskyggn rannsókn á sjúklingum sem gengust undir lungnabrottnám vegna lungnakrabbameins á Íslandi 1988-2007. Kannaðar voru ábendingar aðgerðar, TNM-stig, fylgikvillar, lífshorfur og forspárþættir lífshorfa. NIÐURSTÖÐUR: 77 sjúklingar (meðalaldur 62,3 ár, 64% karlar) gengust undir lungnabrottnám, í 44% tilfella hægra megin. Miðmætisspeglun var gerð í 31% tilfella. Stigun eftir aðgerð sýndi að 41 sjúklingur (54%) var á stigi I+II, 27 (38%) á stigi IIIA/B og ...